Fenomena Online Grooming terhadap Anak Korban Kekerasan Seksual Ditinjau dari Perspektif Viktimologi Kritis - Oktaviana Ayu Sekar Astuti; Sevy Septiana Afina; Peter Guntara (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Online grooming has become a serious form of child sexual exploitation as digital platforms increasingly influence children's social interactions. This study examines online grooming against child victims of sexual violence through the perspective of critical victimology, which highlights structural and institutional factors contributing to victimisation rather than viewing children as passive victims. Using a normative juridical method supported by qualitative literature review, this research analyses legal regulations, court decisions, and recent scholarly sources to evaluate the stages of online grooming, children's vulnerability, and the effectiveness of Indonesia's legal framework, including the Child Protection Law, Pornography Law, Electronic Information and Transactions Law, and Sexual Violence Crime Law. The findings show that Indonesian law lacks a specific provision addressing the preparatory and communication-based stages of grooming, as existing regulations generally require completed sexual acts, explicit content, or physical contact. Comparative analysis with Australia's grooming offence and the Lanzarote Convention highlights the need for legal reform. This study recommends revising Article 76E of the Child Protection Law, strengthening digital platform responsibilities, and providing psychosocial recovery mechanisms for child victims.